Multi-objective synergistic optimization of closed Brayton cycle superstructure for thermal protection system of high-Mach-number air-breathing vehicles - Chendi Yang; Hang Pu; Lin Mu; Lin Zhou; Junjiang Bao; Yining Zhang; Ming Dong (Case Studies in Thermal Engineering)
The power generation and cooling Brayton cycle system promises to resolve the thermal protection and electricity demand of high-Mach-number air-breathing vehicle engines. A new design challenge arises from the trade-off between the cooling capability and thermodynamic performance of the Brayton cycle system under a finite cold source constraint. In this study, a multi-objective synergistic optimization of Brayton cycle configurations, working fluids, and design parameters was investigated using the superstructure method. The hydrocarbon fuel consumption and the thermal efficiency were adopted as the evaluation indexes. The distribution patterns of eight cycle configurations and nine working fluids on the Pareto-front were analyzed under different design parameters. Results show that with the increasing hydrocarbon fuel consumption and thermal efficiency, the main configuration on the Pareto-front transitions from a single regeneration and reheating cycle to a dual regeneration and reheating cycle, and the working fluid transitions from N2O and CO2 to C2H6. The fuel consumption of the trade-off solutions decreases by 19.24 %–39.56 %, and the thermal efficiency increases by 19.98 %–56.89 % when the turbine inlet temperature increases from 400 to 600 °C. The dual regeneration and reheating Brayton cycle with N2O as the working fluid can trade-off between the cooling capability and thermodynamic performance.